Pemanfaatan Ruang Publik Pada Kawasan Rumah Toko di Kecamatan Panakkukang Makassar - Arsyad, Nashrah (Universitas Muslim Indonesia, 2016)
Public spaces in urban areas play a significant role in the growth and development of cities. Their existence is an inseparable part of the buildings in urban environments. As a medium that connects and links various functions of urban areas, public spaces are widely utilized by communities for economic activities, social interactions, or simply for light recreation. However, the planning and design of public spaces have not received serious attention to adequately accommodate urban community activities. Economic growth has spurred the development of shophouses in several cities, including Makassar, in response to housing needs and economic demands. The development of shophouse areas should be balanced with the provision of facilities and infrastructure according to their demands and needs. However, in its development, the construction of shophouses has become uncontrolled due to economic pressures. Considering their function, shophouses, abbreviated as